2019
DOI: 10.1155/2019/3192351
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Therapy of Silymarin (Milk Thistle) on Antituberculosis Drug-Induced Liver Injury: A Meta-Analysis of Randomized Controlled Trials

Abstract: Background Prophylactic therapy with silymarin to prevent the development of antituberculosis drug-induced liver injury (anti-TB DILI) has been under debate. We aimed to evaluate the effect of silymarin in the prevention of anti-TB DILI. Methods We searched MEDLINE, PubMed, Embase, and Cochrane Central Register of Controlled Trials (CENTRAL) up to 30th November 2018. Randomized controlled trials (RCTs) that compared silymarin and placebo to prevent anti-TB DILI were included. All statistical analyses were cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 43 publications
2
22
0
2
Order By: Relevance
“…Overall, silymarin significantly reduced the occurrence of anti-TB/antipsychotic DILI compared to the control group and no significant adverse reaction was found. Under the premise of consistent doses, the results were similar to those reported by Tao et al (19). The optimal treatment time for silymarin for preventing anti-TB/antipsychotic DILI was four weeks.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Overall, silymarin significantly reduced the occurrence of anti-TB/antipsychotic DILI compared to the control group and no significant adverse reaction was found. Under the premise of consistent doses, the results were similar to those reported by Tao et al (19). The optimal treatment time for silymarin for preventing anti-TB/antipsychotic DILI was four weeks.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, it was important to evaluate whether silymarin has a liver-protecting (17) reported that silymarin had no significant effect on anti-TB DILI, but instead it caused liver damage, suggesting that silymarin may be ineffective in anti-TB DILI. However, Tao et al (19) reported that silymarin significantly reduced the incidence of anti-TB DILI and for four-week treatment was the best duration to protect the liver. It indicated that the treatment time is one of the effective factors in the treatment of anti-TB DILI with silymarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOD enzyme whose purpose appears to reduce the harmful effects due to hydroxyl radical ( • OH − ) by scavenges O − 2 to H 2 O 2 consequently, reduction of SOD level indicates hepatic injury. Similarly, CAT enzyme degrades H 2 O 2 into water and oxygen to protect tissue from reactive oxygen species [40][41][42][43]. The risks of hepatotoxicity were raised because of an increase of free radicals and a lack of scavenging capacity of hepatocytes because of increased rates of antioxidant biomarkers [44].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that many drugs undergo hepatic metabolism and can induce, directly or through their active metabolites, hepatotoxicity. As has been observed with anti-tuberculosis drugs (ATDs), this may result in increased morbidity or mortality [87]. Hepatotoxicity may necessitate treatment discontinuation, drug interruption and substitution or dose adjustment [87].…”
Section: Drug-induced Liver Injurymentioning
confidence: 99%